Parallel Programming with transactional memory. - DREPPER, ULRICH (Communications of the ACM, 2009)
The article discusses the manner in which transactional memory can ease parallel computer programming. The increased number of execution units, or CPU (Central Processing Unit) cores, provided by CPU manufacturers is allowing programmers to increased the speeds of applications, the author states. Topics of discussion include multiple paths of execution having to work together to complete tasks, attempting to split a computer program into multiple pieces that can be executed in parallel, and the controlled fashion required to write access to shared data.